2018
DOI: 10.1016/j.biopsych.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Proteomic, Transcriptomic, and Epigenetic Stress Responses in Dorsal and Ventral Hippocampus

Abstract: These findings underscore the importance of considering dorsal and ventral hippocampus separately when conducting high-throughput molecular analyses, which has important implications for fundamental research as well as clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
122
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(137 citation statements)
references
References 79 publications
(100 reference statements)
15
122
0
Order By: Relevance
“…Several studies have previously reported regional and temporally selective IEG activation patterns (Kubik et al 2007). Recently aggregated evidence has made it clear that there is a marked differentiation in both constitutive and behavior-induced transcriptional and translational activity along the axis (Sotiriou et al 2005;Pandis et al 2006;Gusev et al 2005;Leonardo et al 2006;Thompson et al 2008;Dong et al 2009;Snyder et al 2011;Cembrowski et al 2016;Lee et al 2017;Chawla et al 2018;Floriou-Servou et al 2018). The present results extend this evidence indicating that physiological activity patterns can significantly shape transcriptional heterogeneity, which therefore may further support functional heterogeneity along the hippocampus long axis.…”
Section: Implications Of Iegs Expression For Spws Functionsupporting
confidence: 84%
See 1 more Smart Citation
“…Several studies have previously reported regional and temporally selective IEG activation patterns (Kubik et al 2007). Recently aggregated evidence has made it clear that there is a marked differentiation in both constitutive and behavior-induced transcriptional and translational activity along the axis (Sotiriou et al 2005;Pandis et al 2006;Gusev et al 2005;Leonardo et al 2006;Thompson et al 2008;Dong et al 2009;Snyder et al 2011;Cembrowski et al 2016;Lee et al 2017;Chawla et al 2018;Floriou-Servou et al 2018). The present results extend this evidence indicating that physiological activity patterns can significantly shape transcriptional heterogeneity, which therefore may further support functional heterogeneity along the hippocampus long axis.…”
Section: Implications Of Iegs Expression For Spws Functionsupporting
confidence: 84%
“…These, represent endogenous mechanistic aspects of the more general concept of functional segregation along the dorsoventral axis of hippocampus postulating that specific behavioral functions can be ascribed to distinct segments along the hippocampal formation, usually and shortly expressed by a dichotomy between cognition and emotionality related processes undertaken by the dorsal (DH) and the ventral hippocampus (VH) respectively (Bannerman et al 2014;Strange et al 2014;Gulyaeva 2018). The recently revealed striking diversification in patterns of gene expression along the hippocampus (Sotiriou et al 2005;Pandis et al 2006;Gusev et al 2005;Leonardo et al 2006; Thompson et al 2008;Dong et al 2009;Snyder et al 2011;Cembrowski et al 2016;Lee et al 2017;Chawla et al 2018;Floriou-Servou et al 2018), may have profound functional implications for the hippocampal circuitry and the higher-level functional diversification along hippocampus. However, though some dorsal-ventral differences, for instance in synaptic and cell level have been successfully linked to molecular diversity along the hippocampus (Pandis et al 2006;Dubovyk and Manahan-Vaughan 2018a;Snyder et al 2011;Zhu et al 2018;Floriou-Servou et al 2018;Dubovyk and Manahan-Vaughan 2018b), the functional implications of diversified patterns of gene expression are largely unknown (Tushev and Schuman 2016).…”
Section: Introductionmentioning
confidence: 99%
“…DREADDs viral expression (for both wt-hM3Dq and PVCre-hM4Di) was confirmed by m-Cherry staining using standard immunohistochemistry protocols (Notter et al, 2014, Floriou-Servou et al, 2018. Briefly, after the last MRI session mice were deeply anesthetized using a mixture of Ketamine (100mg/kg; Graeub, Switzerland), Xylazine (10mg/kg; Rompun, Bayer) and Acepromazine (2mg/kg; Fatro S.p.A, Italy) and transcardially perfused with 4% Paraformaldehyde (PFA, pH=7.4).…”
Section: Histological Evaluation Of Transfectionmentioning
confidence: 99%
“…Novelty induces psychological stress and arousal (Feenstra et al, 1995), which often results in efficient memory formation in the daily life (Fenker et al, 2008). Such emotional signaling involves the hippocampus (Kaplan et al, 2014;Knight, 1996) and especially its ventral moiety (Floriou-Servou et al, 2018), whereas encoding of spatial memory has been extensively studied in the dorsal hippocampus (Buzsáki and Moser, 2013). However, functional distinction and interaction between the dorsal and ventral hippocampus largely remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…MCs in the ventral hippocampus have extensive bilateral projections to the dorsal DG (Blasco-Ibáñez and Freund, 1997;Fujise et al, 1997) (Figure 1A). Based on this anatomical finding and the preferential signaling of novelty in the ventral hippocampus (Floriou-Servou et al, 2018), we hypothesized that this long range excitatory pathway could convey novelty signals providing a critical excitatory input to dorsal GCs (Scharfman, 2016), facilitating contextual memory formation.…”
Section: Introductionmentioning
confidence: 99%